Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
University of Johannesburg Institutional Repository (UJ IR)

La saisie conservatoire des navires : Droit bulgare et droit français - Gechev, Siméon (Aix-Marseille Université, 2015)

Le beneficial owner et la saisie d'un navire autre que celui auquel la créance se rapporte - Farnier, Marion (Aix-Marseille Université, 2013)